Epigrafía latina e Historia Antigua - Abascal Palazón, Juan Manuel, 1958- (1995)
This article contains a rapid review of the abundant information furnished by the latin inscriptions to our knowledge of Ancient History. To this effect a rapid balance is made of the latin epigraphs known today and the advances made in the study of their supports and the context of the texts, and the study ends with an evaluation of the architectural function of some of the monuments.
Keywords: Epigrafía; Historia antigua; Inscripciones latinas